Design and development of educational digital game in learning Arabic vocabulary and its impact on university student achievement,motivation and perceived acceptence - Mohammad Taufiq Abdul Ghani (2021)
This study aims to develop an educational digital game (eMufradat) for Arabic language vocabulary learning and examine its effectiveness on learning achievement. Besides, this study also aims to examine the influence between learning achievement, motivation and perceived acceptance. A quasi-experimental design pre and post-test is employed in this study. This studys population includes Arabic language proficiency course students in 18 public universities located in Peninsular Malaysia. A total of 611 non-native Arabic students were selected through a cluster sampling to participate in this study. The students were assigned to a control group consisting of 240 students and a treatment group comprising 371 students. The main data of this study were collected through pre-test and post-test; questionnaires and complimented by a semi- structured interview. The quantitative data were analysed using descriptive analysis, t- test, ANOVA test, and regression analysis, while the semi-structured interview was analysed descriptively and thematically. The result of the t-test indicated that the difference in learning achievement between the control and treatment group was significant (p=0.000). Furthermore, the finding of the ANOVA test revealed that the difference in learning achievement between genders was not significant (p=0.287). Another important finding from the regression analysis is that students motivation and learning achievement significantly affect perceived acceptance (p=0.000). In the meantime, students motivation also has a significant effect on their learning achievement (p=0.000). The analysis from the semi-structured interview conducted among 16 students found to support the result of inferential analyses. In conclusion, the use of educational digital game (eMufradat) increased students achievement and motivation in learning Arabic vocabulary. This study has contributed theoretically in the form of design principles of the educational digital game and contributed practically by producing an effective digital game (eMufradat) for learning Arabic vocabulary as well as demonstrates the development of educational digital game practically.